EARTHQUAKE RELOCATION IN GREECE USING A UNIFIED AND HOMOGENIZED SEISMOLOGICAL CATALOGUE - Karakonstantis, A.; Papadimitriou, P. (Bulletin of the Geological Society of Greece, 2010)
In this study phase data from the Cornet seismological network installed by the Geophysics-Geothermics Department (University of Athens) and the permanent networks of the Geodynamic Institute of the National Observatory of Athens and of the Geophysics Department of Thessaloniki (Aristotle University), for the decade 1996-2006, were merged. The data were jointly used to relocate the earthquakes that occurred in the broader area of Greece. Initially, single-event algorithms were applied by minimizing spatiotemporal residuals. Following, the hypocenters were relocated using a doubledifference algorithm where rms, as well as the horizontal and vertical location errors (erh, erz) were minimized and a consequence of that better locations were achieved. After that process the spatial distribution of the epicenters outlined major local tectonic features in Greece. Moreover, the same methodology was applied to the aftershock sequences of large earthquakes and the results were successfully compared with those obtained by available local networks that were deployed.